2022
DOI: 10.3390/cells11162524
|View full text |Cite
|
Sign up to set email alerts
|

S1P-Induced TNF-α and IL-6 Release from PBMCs Exacerbates Lung Cancer-Associated Inflammation

Abstract: Sphingosine-1-phosphate (S1P) is involved in inflammatory signaling/s associated with the development of respiratory disorders, including cancer. However, the underlying mechanism/s are still elusive. The aim of this study was to investigate the role of S1P on circulating blood cells obtained from healthy volunteers and non-small cell lung cancer (NSCLC) patients. To pursue our goal, peripheral blood mononuclear cells (PBMCs) were isolated and stimulated with S1P. We found that the administration of S1P did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Sphingosine levels showed a similar trend, although its levels were much lower than S1P (H S1P median: 131.059 nM vs. H sphingosine median: 0.3215 nM, p < 0.0001; ADK S1P median: 86.629 nM vs. ADK sphingosine median: 0.251 nM, p < 0.0001; SCC S1P median: 108.148 nM vs. SCC sphingosine median: 0.522 nM, p < 0.0001) ( Supplementary Figure S1B ). Because we already demonstrated that lung cancer epithelial cells synthetize and release high levels of S1P [ 19 ], and that circulating S1P acts on its receptors both on lung cancer tissues [ 3 , 19 ] and circulating cells [ 32 ], these data may imply either that S1P from the plasma is driven toward receptors in the case of ADK patients, or that a compromised or non-relevant S1P metabolism/synthesis occurs in the SCC histotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingosine levels showed a similar trend, although its levels were much lower than S1P (H S1P median: 131.059 nM vs. H sphingosine median: 0.3215 nM, p < 0.0001; ADK S1P median: 86.629 nM vs. ADK sphingosine median: 0.251 nM, p < 0.0001; SCC S1P median: 108.148 nM vs. SCC sphingosine median: 0.522 nM, p < 0.0001) ( Supplementary Figure S1B ). Because we already demonstrated that lung cancer epithelial cells synthetize and release high levels of S1P [ 19 ], and that circulating S1P acts on its receptors both on lung cancer tissues [ 3 , 19 ] and circulating cells [ 32 ], these data may imply either that S1P from the plasma is driven toward receptors in the case of ADK patients, or that a compromised or non-relevant S1P metabolism/synthesis occurs in the SCC histotype.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of ceramides into sphingosine and S1P is prompted by the activation of the ceramidases (ASAH1 and 2, ACER1, 2 and 3) ( Figure 4 A, orange squares). ASAH1 is the most studied ceramidase; we have demonstrated its involvement in lung cancer [ 3 , 18 , 19 , 32 ]. According to the RNAseq database (TCGA_LUSC_2016), male and female non-cancerous lung tissues expressed similar levels of mRNA ASAH1 ( Figure 5 A; male mean expression: 1.72 vs. female mean: 1.737; p = 0.53).…”
Section: Resultsmentioning
confidence: 99%
“…In lung cancer, high expression of S1P increases the release of TNF-α and IL-6 from PBMC of lung cancer origin. Compared to the SPHK2 inhibitor Opaganib, which only reduces the release of IL-6 from PBMC of lung cancer origin, inhibition of SPHK1 by PF543 can down-regulate both TNF-α and IL-6 release and more effectively inhibit lung cancer progression [45]. The SPHK1-specific inhibitor SKI-II has also been reported to specifically inhibit the growth of human acute myeloid leukemia cells in vitro while being safe for PBMC from healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipid signaling was linked to TME modifications and resistance of cancer cells to NK cell-based elimination [ 267 ]. For instance, S1P-stimulated lung cancer-derived monocytes secreted TNF-α and IL-6 in S1P receptor 3 (S1P3)/mTOR/K-Ras-dependent manner, while NF-κB was not implicated [ 268 ]. The authors suggested that greater presence of S1P within the TME of lung cancer may orchestrate tumorigenic immune responses [ 268 ].…”
Section: Sphingolipids As Mediators Facilitators and Inhibitors Of Tn...mentioning
confidence: 99%
“…For instance, S1P-stimulated lung cancer-derived monocytes secreted TNF-α and IL-6 in S1P receptor 3 (S1P3)/mTOR/K-Ras-dependent manner, while NF-κB was not implicated [ 268 ]. The authors suggested that greater presence of S1P within the TME of lung cancer may orchestrate tumorigenic immune responses [ 268 ]. However, this statement requires experimental confirmation, as the exact mechanisms (specific S1P targets) of this effect remain unclear and/or controversial [ 269 , 270 ].…”
Section: Sphingolipids As Mediators Facilitators and Inhibitors Of Tn...mentioning
confidence: 99%